Endocrine Requirements for Oocyte Maturation Following hCG, GnRH Agonist, and Kisspeptin During IVF Treatment - Abbara, Ali; Hunjan, Tia; Ho, Vu N. A.; Clarke, Sophie A.; Comninos, Alexander N.; Izzi-Engbeaya, Chioma; Ho, Tuong M.; Trew, Geoffrey H.; Hramyka, Artsiom; Kelsey, Tom; Salim, Rehan; Humaidan, Peter; et al. (Frontiers in Endocrinology, 2020)
Objective The maturation of oocytes to acquire competence for fertilization is critical to the success of in vitro fertilization (IVF) treatment. It requires LH-like exposure, provided by either human chorionic gonadotropin (hCG), or gonadotropin releasing hormone agonist (GnRHa). More recently, the hypothalamic stimulator, kisspeptin, was used to mature oocytes. Herein, we examine the relationship between the endocrine changes following these agents and oocyte maturation. Design Retrospective cohort study. Methods Prospectively collected hormonal data from 499 research IVF cycles triggered with either hCG, GnRHa, or kisspeptin were evaluated. Results HCG-levels (121 iU/L) peaked at 24 h following hCG, whereas LH-levels peaked at ~4 h following GnRHa (140 iU/L), or kisspeptin (41 iU/L). HCG-levels were negatively associated with body-weight, whereas LH-rises following GnRHa and kisspeptin were positively predicted by pre-trigger LH values. The odds of achieving the median mature oocyte yield for each trigger were increased by hCG/LH level. Progesterone-rise during oocyte maturation occurred precipitously following each trigger and strongly predicted the number of mature oocytes retrieved. Progesterone-rise was positively associated with the hCG-level following hCG-trigger, but negatively with LH-rise following all three triggers. The rise in progesterone per mature oocyte at 12 h was greater following GnRHa- than following hCG- or kisspeptin-triggers. Conclusion The endocrine response during oocyte maturation significantly differed by each trigger. Counter-intuitively, progesterone-rise during oocyte maturation was negatively associated with LH-rise, even when accounting for the number of mature oocytes retrieved. These data expand our understanding of the endocrine changes during oocyte maturation and inform the design of future precision-triggering protocols.